Comparision of Spreading Sequences Applied to QS-CDMA Systems - Paul Jean Etienne Jeszensky; André Seichi Ribeiro Kuramoto; Taufik Abrão (Semina: Ciências Exatas e Tecnológicas, 2002)
In this work Walsh-Hadamard, QS-Sequence, Optimal PN, PS and SP spreading sequences characteristics are compared. The comparison is accomplished analyzing the correlation properties and performance of conventional receiver using each one of the sequences in AWGN channels and loads of similar systems in quasi-synchronous condition.